1990
DOI: 10.1038/nbt0990-854
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture on a Thermo-Responsive Polymer Surface

Abstract: We have used a thermo-responsive polymer, poly-N-isopropyl acrylamide (PNI-PAAm), as a substratum for the culture of human dermal fibroblasts by conjugating it with collagen. The cells attached well, spread, and grew on the substratum, indicating that the polymer has no toxicity towards the cells. PNIPAAm is insoluble in water over the lower critical solution temperature (LCST; about 32 degrees C) and reversibly solubilized below the LCST. Taking advantage of this conversion, monolayered fibroblasts cultured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
208
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(212 citation statements)
references
References 10 publications
3
208
0
1
Order By: Relevance
“…The use of thermoresponsive substrate to detach the confluent cell sheets without the use of conventional enzymatic treatments was first reported by Takezawa et al in 1990 (Takezawa et al, 1990). In this study they have used PIPAAm as a substratum by conjugating it with collagen for the culture of human dermal fibroblasts.…”
Section: Various Thermoresponsive Substrates For Cell Sheet Engineeringmentioning
confidence: 99%
“…The use of thermoresponsive substrate to detach the confluent cell sheets without the use of conventional enzymatic treatments was first reported by Takezawa et al in 1990 (Takezawa et al, 1990). In this study they have used PIPAAm as a substratum by conjugating it with collagen for the culture of human dermal fibroblasts.…”
Section: Various Thermoresponsive Substrates For Cell Sheet Engineeringmentioning
confidence: 99%
“…Such approach can be repeated to laminate multiple single cell layers to form thicker matrix. This technology is pioneered by Japanese group [84,85,110] and has been systemically applied to a number of applications such as cornea [82] in clinical trials and myocardium [106] in preclinical trials. The same approach has been modified and improved to produce patterned substrates for thicker tissue fabrication and for injectable applications [57].…”
Section: Scaffolding Approaches In Tissue Engineeringmentioning
confidence: 99%
“…The first reported switch was thermally actuated, using the thermo-responsive polymer poly N-isopropyl acrylamide (PNIPAAm), which is hydrophobic above the lower critical solubility temperature (LCST, ∼32 °C) and very hydrophilic below the LCST. Takezawa et al 59 conjugated PNIPAAm to collagen as a substrate for culturing of human dermal fibroblasts and showed that cells could spread and grew normally on this surface above the LCST but could be detached by lowering the temperature below the LCST without the use of conventional (damaging) enzymes such as trypsin. Without compromised functions found in cultured cells damaged by trypsinization, cells recovered by this method maintained substrate adhesivity, growth, and secretion activities similar to those of primary cultured cells.…”
Section: Iiib Switchable Substratesmentioning
confidence: 99%